A lady's guide to scandal - Irwin, Sophie (Penguin Books, 2023)
"When shy Miss Eliza Balfour married the austere Earl of Somerset, twenty years her senior, it was the match of the season--no matter that he was not the husband Eliza wanted. Now, ten years later, Eliza is widowed. Suddenly, she is left titled, rich, and, for the first time in her life, utterly in control of her own future. She's always lived by society's conventions, but now, Eliza has resolved to do as she wants. And what she wants is to head to Bath with her cousin Margaret, pursue painting, learn to drive, and flirt with Bath's most alluring new resident, the infamous Lord Melville. But when the ripples of Eliza's behavior reach her late husband's nephew--who broke Eliza's heart, years ago--Eliza will learn that freedom does not come without consequences. The only way to ensure she can keep her fortune is to avoid all scandal--but where's the fun in that?"--